2007
DOI: 10.1002/adfm.200601248
|View full text |Cite
|
Sign up to set email alerts
|

Tough, Semiconducting Polyethylene‐poly(3‐hexylthiophene) Diblock Copolymers

Abstract: Semiconducting diblock copolymers of polyethylene (PE) and regioregular poly(3‐hexylthiophene) (P3HT) are demonstrated to exhibit a rich phase behaviour, judicious use of which permitted us to fabricate field‐effect transistors that show saturated charge carrier mobilities, μFET, as high as 2 × 10–2 cm2 V–1 s–1 and ON‐OFF ratios, Ion/Ioff ∼ 105 at contents of the insulating PE moiety as high as 90 wt %. In addition, the diblock copolymers display outstanding flexibility and toughness with elongations at break … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
243
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(247 citation statements)
references
References 26 publications
3
243
0
1
Order By: Relevance
“…111 The first example of such a material, a P3HT (2b)-b-polyethylene (PE) copolymer reached a maximum strain of 660% with a composition of 10/90% P3HT (2b)-b-PE. 112 This copolymer also exhibited impressive conduction properties. The copolymer with only 10 wt% P3HT (2b) resulted in a field-effect transistor charge mobility of 2 × 10 − 2 cm 2 V − 1 s − 1 , whereas systems with 35 wt% P3HT (2b) showed mobilities approaching those of pure P3HT.…”
Section: Block and Random Copolymersmentioning
confidence: 94%
See 3 more Smart Citations
“…111 The first example of such a material, a P3HT (2b)-b-polyethylene (PE) copolymer reached a maximum strain of 660% with a composition of 10/90% P3HT (2b)-b-PE. 112 This copolymer also exhibited impressive conduction properties. The copolymer with only 10 wt% P3HT (2b) resulted in a field-effect transistor charge mobility of 2 × 10 − 2 cm 2 V − 1 s − 1 , whereas systems with 35 wt% P3HT (2b) showed mobilities approaching those of pure P3HT.…”
Section: Block and Random Copolymersmentioning
confidence: 94%
“…The copolymer with only 10 wt% P3HT (2b) resulted in a field-effect transistor charge mobility of 2 × 10 − 2 cm 2 V − 1 s − 1 , whereas systems with 35 wt% P3HT (2b) showed mobilities approaching those of pure P3HT. 112 This results from the low percolation threshold, or the minimum concentration to achieve a continuous interconnecting pathway for charge transport, in the P3HT material when either blended or copolymerized with a polymer that crystallizes. These systems need only 10% P3HT to form co-continuous domains, a trend also observed in other P3HT copolymer systems.…”
Section: Block and Random Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, therefore, essential to postprocess after deposition of the block copolymer thin film, as shown in Figure 20, where solvent annealing was used to order the block copolymer. 143 Mü ller et al 206 synthesized a diblock copolymer of poly(3-hexylthiophene)-block-polyethylene (P3HT-b-PE) and observed that this system has good conductive properties alongside mechanical toughness, both qualities that are desirable for flexible solar cells. Although not strictly concerned with making OPVs from this material, it shows the possibilities of a double crystalline diblock system.…”
Section: Processingmentioning
confidence: 99%